Political Law of Corruption Eradication in Indonesia (Case Study on the Corruption of Sugar Import Corruption of the Minister of Trade in 2015) - Br Sembiring, Tamaulina; Ismaidar; Ismed (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study is to examine in depth the polemic of law enforcement of corruption crimes (a case study of sugar imports by the Minister of Trade Thomas Lembong) and comprehensively discuss the legal and political framework for the eradication of corruption in Indonesia. The type of research is normative juridical with a descriptive-analytical approach, discussing existing legal symptoms and problems and testing them based on laws regulations, and legal norms. The results of this study show that the analysis of the handling of the case of alleged corruption in Thomas Lembong's sugar imports has many problems, including the requirement for political interests, not following the procedure and the time for determining the suspect is very long, the amount of state losses is uncertain, there is not enough evidence and only focuses on one individual. Corruption as an extraordinary crime requires extraordinary handling, including penal policies regulated in several regulations such as the law on the eradication of corruption crimes, the law on the corruption eradication commission, the Criminal Code, to the Presidential Regulation on the national strategy for corruption prevention, as well as non-penal policies including: public awareness education, administrative reform and strengthening of supervisory institutions